The Influence of Human Resource Development on Employee Performance in the Assets and Investment Section of the Medan Mayor's Office - Indah Lestari, Annio; Hasby, Muhammad; Darma Yuni, Ika (Taqaddum: Community Service Journal, 2023)
In the world of work, things can certainly be found that are contrary to the performance of workers towards their work. And there are still strange things found at work that do not support the values of work discipline. Human resources have a very vital role and need serious attention. Workers or employees as human resources are very important in improving the performance or progress of a company, this study was conducted with the aim of determining the extent to which human resource development influences employee performance in the Asset and Investment Section of the Medan Mayor's Office. The results of the study conducted in the asset and investment section of the Medan Mayor's Office using the interview method with office employees, resulted in researchers getting results. It turns out that by using all means and developing human resources in this office such as training, evaluation and improving performance, human resources in this office become better. Through an approach with training specifically designed to improve employee competence, it is hoped that the data obtained is data that is reliable and of high value. In addition, researchers also perfected it by looking for references from previous studies so that the contents of the results produced were even better.Keywords:Performance Analysis; HR Development